(untitled) - Bradley, Julia Case (Boston, 2003)
Advanced Programming in Visual Basic.NET", by best-selling authors Bradley & Millspaugh, maintains the strong pedagogy that has been used to teach students how to program in Visual Basic since VB 4.0. Instructors and students like this book because it does not just teach Visual Basic, it incorporates basic concepts of programming, problem solving, and programming logic. "Advanced Programming in Visual Basic.NET" has been completely revised: including the text, website, and instructor's materials
Keywords: Microsoft Visual BASIC,BASIC ( Computer program language )